Characterization of leukemic cell behaviors in a soft marrow mimetic alginate hydrogel - Vu, Thao Thi Thu (2013)
Alginate hydrogels possess tunable mechanical properties that can mimic soft marrow tissue and present three-dimensional (3D) cues. This study evaluates its utility for supporting leukemic cell growth in vitro and its impact on cell survival, growth, and differentiation. Our results showed that the standard viscosity alginates had compromised leukemia cell viability but lower viscosity alginates recovered cell viability and improved 3D cell proliferation (27 fold) compared to 2D cultures (18 fold). Conjugation with RGD peptides promoted further cell growth (43 folds). In general, 3D hydrogels supported high-density cultures better than 2D cultures. Leukemic cells formed densely packed cell clusters in alginate hydrogels and spontaneously differentiated into a more diverse myeloid population. The cell cycle data suggested that more cells go into active cycling with a G2/M arrest in alginate hydrogels and the presence of multiploidy confirmed maturation toward megakaryocytes. In summary, superior culture of leukemia cells in 3D hydrogels is demonstrated in this study accompanied by a potential role of physical cues influencing cell fate decision. Manipulation of biophysical and biochemical properties of alginate hydrogels permits the study of specific interactions and serves to provide a robust 3D platform for studying extrinsic contributions inside the bone marrow.